traT and CNF2 genes of Escherichia coli isolated from milk of healthy cows and sheep - Açik, MN; Yurdakul, NE; Çakici, L; Onat, N; Dogan, Ö; Çetinkaya, B (Elsevier Sci Ltd, 2004)
The objectives of the present study were to isolate Escherichia coli from milk of apparently healthy cows and sheep and to investigate the presence of traT and cytotoxic necrotising factor-2 (CNF2) virulence genes by multiplex polymerase chain reaction (PCR). Milk samples collected from a total of 1028 apparently healthy ruminants (737 cows and 291 sheep) in eastern Turkey were streaked onto 5% sheep-blood agar. E. coli was isolated and identified by biochemical tests in 5.9%, (61/1028) of milk samples. Correct amplification with the molecular length of 23:2 bp was obtained from all E coli isolates by the species-specific PCR. The isolation rates of the agent were calculated to be 7.6% (56/737) in cows and 1.7% (5/291) in sheep. The difference between these proportions was statistically significant (p<0.001). Multiplex PCR showed that traT and CNF2 genes were present in 62.3% and 6.6% of all isolates, respectively. Both genes were present in 16.4% of the isolates, with only 14.7% having neither gene. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: E. coli; traT; CNF2; milk; cow; sheep